Elektrolisis: Proses Elektrolisis Campuran Larutan Tembaga(II) Sulfat (CuSO4) Dan Aluminium Sulfat (Al2(SO4)3 Menggunakan Elektroda Karbon - Ramadhan, Luthfi; Najmi Nur Asyifa Ali (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research explores the electrolysis process of a mixture of copper(II) sulfate (CuSO4) and aluminum sulfate (Al2(SO4)3) solutions using carbon electrodes. The main objective is to understand the mechanism of gas formation and metal deposition efficiency. In the experiment, CuSO4 and Al2(SO4) solutions )3 with a concentration of 0.5 M each is used as the electrolyte, and carbon electrodes as the cathode and anode. During electrolysis, the electric current causes copper ions (Cu²⁺) to move to the cathode, undergo reduction to copper (Cu), and deposit on them. cathode. Aluminum ions (Al³⁺) tend to remain in solution due to the higher reduction potential. At the anode, hydroxide ions (OH⁻) from water are oxidized, producing oxygen gas (O₂). and oxygen gas at the anode. The efficiency of copper deposition was analyzed by measuring the mass of deposited copper. This research provides insight into the dynamics of electrolysis of CuSO4 and Al2(SO4)3 mixtures, as well as their potential in electrochemical applications. In conclusion, the use of carbon electrodes is effective for the deposition of pure copper and the production of oxygen gas as a by-product.